2012
DOI: 10.1177/0022034512445633
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Engineered Bone with Adipose Stromal Cells from Buccal Fat Pad

Abstract: A robust method for inducing bone formation from adipose-derived stromal cells (ADSCs) has not been established. Moreover, the efficacy of strong osteogenic inducers including BMP-2 for ADSC-mediated bone engineering remains controversial. Meanwhile, the buccal fat pad (BFP), which is found in the oral cavity as an adipose-encapsulated mass, has been shown to have potential as a new accessible source of ADSCs for oral surgeons. However, to date, there have been no reports that define the practical usefulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…A total of 10 articles met the inclusion criteria and were included in the analysis (Figure 1). Of these 10 studies, seven were conducted in vitro [9, 1217], and the other three were conducted both in vitro and in vivo [10, 11, 18]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 10 articles met the inclusion criteria and were included in the analysis (Figure 1). Of these 10 studies, seven were conducted in vitro [9, 1217], and the other three were conducted both in vitro and in vivo [10, 11, 18]. …”
Section: Resultsmentioning
confidence: 99%
“…Under appropriate conditions, AdSCs derived from BFP (BFPSCs) have been shown to differentiate into chondrocytes, osteoblasts, or adipocytes in vitro [9]. Moreover, Shiraishi et al reported that BFPSCs can form engineered bone in the back subcutaneous pockets of nude mice [10]. Khojasteh and Sadeghi recently used BFPSCs in conjunction with iliac bone block grafts and showed an increase in the amount of new bone formation and a decrease in secondary bone resorption in extensively atrophic jaws [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BFP is a discarded tissue of plastic surgery for cheek reduction. Recent studies showed that human ASCs isolated from the BFP possess all the suitable characteristics for bone tissue engineering, both in vitro [21] and in vivo [22]. Despite the known low immunogenicity of human ASCs, which suggests theoretically their use in preclinical models, we are required to test their safety when implanted in a homologous setting.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to use robust bioactive growth factors as inducers to enhance ADSC osteogenic differentiation during bone regeneration. 10 PDGF-BB, a member of the PDGF family, has exhibited effects on enhancing both proliferation and osteogenesis. 11 More importantly, PDGF-BB is FDA approved for use in the treatment of local periodontal defects and diabetic ulcers.…”
Section: Introductionmentioning
confidence: 99%